2020
DOI: 10.3390/ijerph17207621
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Emotional Intelligence Intervention and Its Impact on Academic Performance in Spanish Pre-Adolescent Elementary Students: Results from the EDI Program

Abstract: There is clear agreement about the importance of promoting emotional intelligence in school through programs integrated in the academic curriculum. The objective of this study is to analyze the impact of the EDI program on the emotional intelligence trait and on general academic performance, as well as mathematics and language performance. The participants were 5th grade elementary school students between 10 and 11 years old. A quasi-experimental repeated-measures design was used, with a comparison group and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(48 reference statements)
1
2
1
1
Order By: Relevance
“…Moreover, several reviews and meta-analyses provide evidence to consider emotional intelligence as a trainable ability in adults (Hodzic et al, 2018;Kotsou et al, 2019;Mattingly and Kraiger, 2019). Nonetheless, some intervention programs also have found that emotional intelligence can be trained in adolescents (e.g., Motamedi et al, 2017;Viguer et al, 2017;Cantero et al, 2020). In line with our findings, researchers and practitioners should foster the development of students' emotional intelligence, particularly among those who have low-quality relationships with their teachers.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, several reviews and meta-analyses provide evidence to consider emotional intelligence as a trainable ability in adults (Hodzic et al, 2018;Kotsou et al, 2019;Mattingly and Kraiger, 2019). Nonetheless, some intervention programs also have found that emotional intelligence can be trained in adolescents (e.g., Motamedi et al, 2017;Viguer et al, 2017;Cantero et al, 2020). In line with our findings, researchers and practitioners should foster the development of students' emotional intelligence, particularly among those who have low-quality relationships with their teachers.…”
Section: Discussionsupporting
confidence: 84%
“…It does, however, require a really progressive effect. Although fact has been much research on the subject, the findings show a robust correlation between EI intervention programs (EI training) and EI (Cantero, Bañuls & Viguer, 2020;Gilar-Corbi, Pozo-Rico, Pertegal-Felices & Sanchez, 2018). The current analysis did discover a coefficient Beta value of 0.096, though.…”
Section: The Discussion and Resultscontrasting
confidence: 58%
“…La evidencia aportada tiene una implicación fundamental para la prevención del PSU: estudios meta-analíticos y de revisión sistemática han concluido que la IE es una capacidad que puede desarrollarse de forma eficaz por medio de intervenciones guiadas (Hodzic et al, 2018;Kotsou et al, 2019;Mattingly y Kraiger, 2019). Asimismo, algunos estudios en los que se ha trabajado específicamente con población adolescente han encontrado que los programas de intervención que pretenden mejorar la IE, además de ser efectivos aumentando dicha capacidad (Motamedi et al, 2017;Viguer et al, 2017), también tienen repercusiones en otras áreas, como el rendimiento académico (Cantero et al, 2020) y los niveles de agresividad de los adolescentes (Castillo-Gualda et al, 2019;Hojjat et al, 2017).…”
Section: Referenciasunclassified